Effect of Body Condition Score on Productive Performance of Local Karadi Cows - Ahmed, Bahroz M. S.; Maarof, Nazhad N.; Petrus, Talal Y. (Sulaimani Journal for Pure and Applied Sciences, 2010)
Twenty one Karadi cows raised at Bakrajo Farm, College of Agriculture, University of Sulaimani, Kurdistan Region, Iraq, over the period April 2006 – May 2007 were used in this study. Cows were naturally mated, then calved between 13th of June 2006 and 21st of January 2007. Cows were scored according to the East of Scotland College of Agriculture system (ESCA) for their body condition at two periods; sixty days before the expected calving, and at calving (1-3 days after calving). Data were analyzed using the General Linear Model (GLM) procedure system by Statistical Analysis System (SAS). The overall means of milk yield of 8 weeks, total milk yield, peak milk yield, persistency, and lactation period were 217.76 ± 18.13 kg, 290.43 ± 34.10 kg, 35.00 ± 2.69 kg/week, 4.29 ± 0.28 week, and 89.38 ± 7.01 days, respectively. Body condition score at drying off and at calving had a significant effect on 8 weeks, total milk yield, peak milk yield and persistency. Lactation period was affected by body condition score at drying off, whereas body condition score at calving not affected the former trait. Parity and season of calving not affected the former traits.
Keywords: Karadi cows; Sulaimani; body condition score; milk yield; parity; season of calving; peak milk yield; persistency; lactation period